CSR and Taxes: Examining the Taxing Debate Over a Corporate's Social Responsibility - Buberwa, Kemilembe (Graduate School of Business (GSB), 2024)
Emerging research has sought to understand if there is a relationship between corporate taxes and corporate social responsibility (CSR); and more specifically, whether the payment of a company's taxes can become an additional consideration when distinguishing between responsible and irresponsible company behaviour. This study adds to this research as it provides an emerging market's perspective. The study analyses companies listed on the Johannesburg Stock Exchange (JSE) over a five-year period between 2015 and 2019. Effective tax rate was used as a proxy for corporate tax aggressiveness (CTA), CSR scores were used as a proxy for CSR, and various governance and financial variables were included to control for the effects of tax aggressiveness. The purpose of this study is to understand if there is a relationship between a company's CSR and CTA and, if so, to establish the significance and direction of such a relationship. In addition, the study considered the relationship between CTA and each individual category of CSR (namely community, environment, employee and governance) to uncover the extent to which each was likely to have an impact on CTA. Both research questions were assessed via the pooled ordinary least squares (OLS), random effects and fixed effects methods to select the most appropriate modelling technique. The empirical findings could not find a significant relationship between CSR and CTA. The preliminary analysis found a significantly negative relationship between CTA and three of the control variables (size, leverage and return on assets). The additional analysis found a significantly negative relationship between CTA and the environment category of CSR, as well as a significantly positive relationship between CTA and the community category of CSR. This implies that environmental initiatives are more likely to reduce tax aggressive behaviour, and that community initiatives are more likely to increase tax aggressive behaviour. The additional analysis also found a significantly negative relationship between return on assets and CTA. Emerging markets face significant development funding gaps. Emerging economies would benefit greatly from improved domestic revenue mobilisation as it would reduce the development funding deficit, reduce dependence on foreign aid, and strengthen relations between governments and their citizens. It is recommended that policy discussions should consider the coordination of CSR activities at a national level, the standardisation of integrated reporting requirements, as well as the inclusion of corporate tax planning activities in integrated reports and CSR disclosures.